Pengaruh Pengetahuan Perpajakan, Tingkat Pendapatan, dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Pada Wajib Pajak Kendaraan Bermotor di Kabupaten Buleleng): Studi Kasus pada Wajib Pajak Kendaraan Bermotor di Kabupaten Buleleng - Kadek Sintia Dwi Cahyani; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2023)
This research was conducted with the aim of knowing the effect of the variable knowledge of taxation, level of income, and quality of tax service on taxpayer compliance with motorized vehicles that have been registered at the Buleleng District Samsat Office. This study uses a type of quantitative research by distributing questionnaires using a Likert scale measurement. The sampling method in this study was the Solven formula, with a maximum tolerated error of 5%, so that 400 respondents were obtained from a total of 474,431 motorized vehicle tax obligations. Data analysis in this study used multiple linear regression analysis with the help of SPSS Statistics 26. The findings of this study are that knowledge of taxation and the quality of tax authorities have a positive and significant effect on taxpayer compliance for motorized vehicles, while the level of income has no significant effect on taxpayer compliance motor vehicles